Seawater temperature measured at the surface and at two depths (7 and 12 m) in one coral reef at Culebra Bay, Gulf of Papagayo, Costa Rica - Jiménez, Carlos (2001)
Superficial seawater temperature (SST) and at two depths (7 and 12 m) were measured non-continuously during the study of the corals and coral reefs of Culebra Bay (1993-1996). SST showed seasonal variations of ~4°C. The highest average temperatures (27.0 ± 0.1, range 23-29°C) were during the rainy season from May to November and the lowest (22.9 ± 0.3°C, 15.5-29°C) during the dry season from December to April. Cold fronts with 2-3°C differences in SST frequently pass into the bay and remain there for several hours according to the tidal cycles. Differences of ~3°C between SST and the bottom (5-10 m depth) were usually found, particularly at locations where bottom topography and tidal circulation produced tidal bores. The average temperatures recorded by data loggers placed at 7 and 12 m depth on a coral reef at the outer shores of Culebra Bay, were 27.1 ± 0.02ºC (20.5 – 31.6ºC) and 25.8 ± 0.04 (9.9-31.5ºC) respectively. The seasonal pattern of higher and lower temperatures corresponds respectively to the rainy and dry season of the northern Pacific coast of Costa Rica. Water temperature at 12 m was <14ºC for some hours during an upwelling event whilst minimum temperatures at 7 m were ≥ 22ºC. Negative temperature anomalies coincided with an increase of the NE-E winds intensity and there is a lunar and tidal component which influence diurnal variations of temperature. These results suggest that coral reefs built by branching species (e.g. Pocillopora spp.) in Culebra Bay could be limited by both the influence of cold fronts and by seasonal upwellings which affect negatively those coral species, as reported for other locations in the tropical eastern Pacific.